ANALYSIS OF DIYARBAKIR MANIS IN THE CONTEXT OF FUNCTIONAL - Şenocak, Ebru; Karaman, Gülben (Nigde Omer Halisdemir University, 2025)
Mania; they are oral culture products that reflect the common feelings, values, judgments and reactions of the society, unite generations, and relieve the society mentally, socially, culturally and psychologically. The tradition of chanting mani is not static, but has been shaped by the social, economic and historical conditions of the period in which it was sung; It has gone through different processes in terms of form, content and function. The scope of chanting manis, which is an important source of discovery and analysis in folk culture, has decreased considerably today. In order to compile past cultural values and aesthetic judgments and protect them, and to be inspired by past values while creating our new cultural field, it is necessary to compile the products in the fields that have been said or are being said and bring them to future generations. In this study, forty-six manis were collected from seven informants in Diyarbakır and the manis were evaluated within the scope of Bascom's functional folklore elements. Among the manis discussed within the scope of the theory, the manis with the function of entertaining, amusing and having a good time were found to be the most frequently sung manis in Diyarbakır. Diyarbakır manis have meaning and function-laden features that are appropriate for the purposes and needs of the people of the region. In the collected manis, the cultural and mental accumulation of the people of Diyarbakır, their sense of fun and humor, their material and spiritual sensitivities, and their reactions to social pressure are given directly or indirectly.

Mani; toplumun ortak duygu, değer, yargı ve tepkilerini yansıtan, kuşakları birleştiren, toplumu zihinsel, sosyal, kültürel ve psikolojik yönden rahatlatan sözlü kültür ürünleridir. Mani söyleme geleneği statik olmayıp söylendiği dönemin sosyal, ekonomik ve tarihi şartlarından etkilenerek şekillenmiş; şekil, içerik ve işlev bakımından farklı süreçlerden geçmiştir. Halk kültüründeki keşif ve analizlerin önemli bir kaynağı olan manilerin söylenme sahası, günümüzde oldukça azalmıştır. Geçmişteki kültürel değerleri, estetik yargıları derleyip onlara sahip çıkmak ve yeni kültürel alanımızı oluştururken geçmiş değerlerden feyz almak adına mani söylenmiş/söylenmekte olan sahalardaki ürünleri derleyip gelecek nesillere kazandırmak gerekmektedir. Bu çalışmada; Diyarbakır’da yedi kaynak kişiden derlenen kırk altı mani, yedi kaynak kişiden derlenmiş ve maniler, Bascom’un işlevsel halk bilimi unsurları kapsamında değerlendirilmiştir. Kuram dahilinde ele alınan manilerden eğlenme, eğlendirme ve hoşça vakit geçirme işlevindeki maniler, Diyarbakır’da en çok söylenen maniler olarak tespit edilmiştir. Diyarbakır manileri, bölge halkının amaç ve ihtiyaçlarına uygun söyleyişe sahip, anlam ve işlev yüklü özelliklere sahiptir. Derlenen manilerde, Diyarbakır halkının kültürel ve zihinsel birikimi, eğlenme ve mizah anlayışı, maddi ve manevi yarlılıkları, toplumsal baskı karşısında verdiği tepkiler, doğrudan ya da dolaylı olarak verilmektedir.
İŞLEVSEL HALK BİLİMİ KURAMI BAĞLAMINDA DİYARBAKIR MANİLERİNİN İNCELENMESİ
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)